Word-processor or pencil-and-paper? A comparison of students' writing in Chinese as a foreign language. Issue 3 (2nd April 2016) - Zhu, Yu; Mark Shum, Shiu-Kee; Brian Tse, Shek-Kam; Liu, Jinghui Jack
Abstract : A study is reported of the performance and attainment of 32 students from overseas studying elementary Chinese as a foreign language (CFL) in a Chinese university. With an AB-BA design, they were asked to use two forms of writing media to present two essays: one a word-processed essay entitled "My Favourite Female" and the other a conventional hand-written essay entitled "My Favourite Male". The essays were marked by experienced Chinese language experts and the learners' impression of using each type of writing medium was gathered via questionnaires and interviews. Inferential statistics showed that the students performed significantly better when using a word-processor, and they thought that completing writing tasks using pencil-and-paper and word-processors were markedly different. Most of them felt that their work was more professional when produced on a word-processor. A small number of students considered that writing by hand in Chinese was aesthetically pleasing, but they appreciated the convenience of writing in words spelled and written correctly by the computer. Inter-marker consistency was more homogeneous for essays written on the computer. In conclusion, word-processors are suggested as the preferred writing medium for beginning learners of CFL.